Water-Mediated Rhenium-Catalyzed Photodeoxygenation of Polyfunctional Organic N-Oxides - Joly, Nicolas; Kjellberg, Marianne; Bouchet, Alexis; Nicolas, Emmanuel; Cantat, Thibault; Anthore-Dalion, Lucile (Synthesis, 2025)
The oxidation of N-heterocycles is key to their functionalization as it enhances their reactivity in the ortho position. However, an efficient post-reduction is often required to access the targeted compound. Here, an air-stable rhenium(I)-based photocatalyst enables the fast deoxygenation of N-heterocyclic and alkyl N-oxides, avoiding sacrificial oxophilic reagents. We demonstrate that adding H2O dramatically accelerates the reaction rate. The system tolerates air contamination, is scalable, and shows a high functional group tolerance toward other reducible functions (free alcohol, carboxylic acid, ester, nitrile, halogen, etc.) and light-sensitive N-heterocycles.
Keywords: Pyridine N-oxides; Photocatalysis; Reduction; Synthetic methodology; Rhenium catalysis